The Importance of Innovation in Ensuring Business Sustainability through MSME Product Development - Setiawan, Rahyuniati; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam; Dahlena, Alni; Adiansyah, Adi; ., Isnawati (Entrepreneurship Faculty, Universitas Garut, 2024)
Business sustainability is a manifestation of business success in its ability to meet consumer needs and keep up with the times by continuing to innovate and develop products. The purpose of this study is to identify how important innovation and product development are for business success. The research method with systematic review and meta-analysis is an effective approach to go beyond the limitations of ordinary literature studies. This approach helps researchers gain a deeper understanding of efforts to increase the chances of a business's sustainability. From the results of the study, it can be seen that innovation and product development are the right strategies to make a business survive in tight competition. With the results of this study, business actors can implement it in ongoing businesses to be able to survive amidst competitors, changing trends, and increasing and diverse consumer needs by continuing to innovate and develop existing products to continue to improve business sustainability.